Visual attention to nitrite-free and plant-based sausages alternatives: Effect of information and cross-cultural differences between Ireland and Finland - Melios, Stergios; Crofton, Emily; Tuccillo, Fabio; Häikiö, Tuomo; Sandell, Mari (Elsevier BV, 2026)
Consumers encounter various visual cues while shopping, which influence their food choices. Additionally, concerns related to the use of nitrites in cured meats and the overall impact of animal breeding on the environment are transforming the European cured meat market. The aim of this study was to evaluate the differences in consumer (n = 66) visual attention to three sausages (conventional, nitrite-free, and plant-based) under both blind and informed (health risk, health benefit, and health plus environmental benefit) conditions in Ireland and Finland, using a wearable eye-tracker in combination with a food choice task and Flash Profile. Significant differences were observed in consumer visual attention between the countries. Consumers in Ireland were navigating between products, whereas those in Finland tended to focus on each product (or text) for longer periods without revisiting it. In both countries, most consumers in the blind condition chose the conventional product, followed by the plant-based alternative. In the informed condition, the conventional product remained the most preferred in Ireland, while in Finland, the plant-based alternative became the most popular. In Ireland, visual attention differences between products were minimal, but the nitrite-free sausage information text attracted the most attention. In Finland, however, under the blind condition, the plant-based alternative had significantly more dwells with fixation and revisit count. Lastly, dwell time, was the only measure found to be significant in predicting product choice. These results highlight the need for culture-specific approaches underscoring aspects of visual attention and information provision in driving healthier and sustainable food choices among consumers.